(untitled) (Lapai Journal of Economics, 2023)
This research work examines the role Bank of Agriculture Limited plays in fostering agricultural development in Nigeria. Primary data was obtained by distributing 120 questionnaires to farmers who benefitted from the Bank’s credit facility, linear regression analysis was employed and the result reveals that credit advance contributes 24.13% in increasing farmers’ output which translates to agricultural development. It was therefore recommended that the government should firstly invest in the agricultural sector by making provisional allocations in the annual budget for the Bank; secondly, the Bank should streamline the loan application, processing and approval procedure to ease access to credit; thirdly, enact policy that will mandate civil servants to have personal account with the Bank to help raise the liquidity position of the Bank; and lastly, direct the Central Bank to issue all financial transaction licenses to the Bank including such that would enable the Bank deal in foreign exchange transactions.